1995
DOI: 10.1016/s0741-5214(95)70253-9
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic carotid artery stenosis and stroke in patients undergoing cardiopulmonary bypass

Abstract: It is concluded that carotid atherosclerosis is a risk factor for hemispheric stroke in patients undergoing CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0
11

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(109 citation statements)
references
References 22 publications
3
91
0
11
Order By: Relevance
“…According to world literature critical carotid stenosis is not only cause but the risk factor for stroke/TIA [13][14][15][16]. Moreover, important factors are cerebral hyperperfusion syndrome immediately after CEE, supraventricular rhythm disturbances, low ejection fraction, postoperative hypercoagulability and cerebral embolization by atherothrombotic substances as a result of aortic manipulation [17][18][19].…”
Section: кардиология и сердечно-сосудистая хирургия 2 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…According to world literature critical carotid stenosis is not only cause but the risk factor for stroke/TIA [13][14][15][16]. Moreover, important factors are cerebral hyperperfusion syndrome immediately after CEE, supraventricular rhythm disturbances, low ejection fraction, postoperative hypercoagulability and cerebral embolization by atherothrombotic substances as a result of aortic manipulation [17][18][19].…”
Section: кардиология и сердечно-сосудистая хирургия 2 2017mentioning
confidence: 99%
“…По данным мировой литературы [13][14][15][16], критиче-ские стенозы БЦА скорее являются не единственной при-чиной, а фактором риска развития ОНМК/ТИА. Наряду с этим важными факторами являются такие, как синдром гиперперфузии головного мозга непосредственно после выполнения КЭЭ, суправентрикулярное нарушение рит-ма, низкая фракция выброса (ФВ), послеоперационная гиперкоагуляция, а также эмболизация церебральных ар-терий атеротромботическими субстанциями в результате манипуляций на аорте [17][18][19].…”
unclassified
“…Therefore, screening programs in CABG candidates may identify from 2.8% to 8.7% of the patients with signifi cant carotid lesion (≥ 75%) [28][29][30][31][32][33] .…”
Section: Surgical Indication and Techniquementioning
confidence: 99%
“…The literature has shown that a carotid disease greatly increases the likelihood of stroke following CABG 28,47,48 . Therefore, CE should precede CABG in both the combined and the staged approach, depending on patient condition, availability of surgical teams, and local surgical experience.…”
Section: Surgical Indication and Techniquementioning
confidence: 99%
“…The incidence of having significant carotid disease in patients undergoing coronary artery bypass grafting (CABG) has been reported as 22%. 1) In addition, significant carotid artery stenosis has been shown to be the most powerful predictor of perioperative stroke in patients undergoing cardiac surgery.…”
mentioning
confidence: 99%